FAO fisheries technical paper N134 rev.1 - Fyvind Gulbrandsen (FAO, 1997)
The cost advantage of timber versus other materials is still sufficient to ensure that it will remain the dominant boatbuilding material for a long time to come in developing countries. However, unresticted or illict access to forest resources and the introduction of rational forestry management policies have caused and will continue to cause a scarcity of the sections of timbers froditionally favaured by boatbuilders. The resultant scarcity and high cost of good quality timber have not meant that less wooden boats are being built, but rather that vessel quality has deterionated through the use of interior and inadequate design strength.